2018
DOI: 10.3389/feduc.2018.00011
|View full text |Cite
|
Sign up to set email alerts
|

An Ecological Approach to Understanding Assessment for Learning in Support of Student Writing Achievement

Abstract: In this paper, we report on a project conducted in a New Zealand primary school that aimed to enhance the writing achievement of primary school boys who were achieving just below the national standard for their age or level through the use of peer feedback and information and communication technologies (ICTs). The project involved a teacher collaborative inquiry approach where all seven teachers in the school and the school principal participated to achieve the project aim. We adopt an ecological approach as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The less favorable opinions suggested a mismatch between the requirement of the sociocultural contexts (i.e., the government policy of mandatory online learning due to health risk) and the classroom context into which more learning resources (e.g., strategies of online engagement) should be integrated for students to draw on to enhance the aforementioned three aspects of their feedback literacy. The contrast between students’ positive perceptions of LOA-related resources/activities and their less positive views of the mandated online mode of learning indicated that the teacher should adopt a holistic systemic perspective (Cowie & Khoo, 2018 ) when facilitating student feedback literacy development. As a key agent in creating learning resources in the classroom ecosystem (Q. Liu & Chao, 2018 ), the teacher needs to not only foster synergy between different components of the classroom ecosystem, but also align classroom and sociocultural contexts, given the negative impact of misalignment identified in the study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The less favorable opinions suggested a mismatch between the requirement of the sociocultural contexts (i.e., the government policy of mandatory online learning due to health risk) and the classroom context into which more learning resources (e.g., strategies of online engagement) should be integrated for students to draw on to enhance the aforementioned three aspects of their feedback literacy. The contrast between students’ positive perceptions of LOA-related resources/activities and their less positive views of the mandated online mode of learning indicated that the teacher should adopt a holistic systemic perspective (Cowie & Khoo, 2018 ) when facilitating student feedback literacy development. As a key agent in creating learning resources in the classroom ecosystem (Q. Liu & Chao, 2018 ), the teacher needs to not only foster synergy between different components of the classroom ecosystem, but also align classroom and sociocultural contexts, given the negative impact of misalignment identified in the study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the misalignment between micro- and macro- contexts may aggravate the existing mismatch between learners and classroom eco-system, with such aggravated mismatch further constraining student feedback literacy development (see the elbow double arrows connecting learners and classroom ecosystem, which are thicker than the elbow double arrows connecting micro- and macro- contexts). Previous research from an ecological perspective either focused on the positive influence of the alignment between different levels of contexts in relation to student engagement with feedback (Cowie & Khoo, 2018 ) or emphasized the interplay between learners and contextual factors regarding student feedback literacy (Chong, 2020 ). This study contributed to research on student feedback literacy by revealing not only the negative impact of misalignment between different layers of contexts on student feedback literacy, but also how such misalignment may be connected to the interplay between learners and micro-level factors to shape individual differences in student feedback literacy development when LOA is employed online during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations